Magnetic field effects on the near field spectra of quantum dots - Zora, A.; Simserides, C.; Triberis, G. (Physica Status Solidi (A) Applications and Materials Science, 2005)
We theoretically investigate the linear near field absorption spectra of semiconductor quantum dots under magnetic field of variable orientation. We examine if the application of the magnetic field alone is sufficient to cause – increasing the spot illuminated by the near field probe – “unexpected” features to the absorption spectra.